2013
DOI: 10.1002/chem.201204207
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrosynthesis of Ketones from Benzylic Methylenes by Electrooxidative CH Activation

Abstract: Electrify your chemistry! Direct electrosynthesis of ketones from benzylic methylenes in an undivided cell was realized in moderate to good yields. In this electrosynthesis, electrons instead of conventional oxidants and catalysts are employed to make the reaction environmentally benign. Moreover, the reaction intermediate radical was detected by ESR spectroscopy and the reaction mechanism was clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 42 publications
1
28
0
1
Order By: Relevance
“…278 Wang and co-workers demonstrated that the benzyl cation arising from direct anodic oxidations could be intercepted with water whereupon further oxidation of the resulting benzyl alcohol furnishes the ketone (Figure 17B). 279 This process is most effective for methylene units substituted with two arenes; lower yields were noted otherwise.…”
Section: Anodic Oxidationmentioning
confidence: 99%
“…278 Wang and co-workers demonstrated that the benzyl cation arising from direct anodic oxidations could be intercepted with water whereupon further oxidation of the resulting benzyl alcohol furnishes the ketone (Figure 17B). 279 This process is most effective for methylene units substituted with two arenes; lower yields were noted otherwise.…”
Section: Anodic Oxidationmentioning
confidence: 99%
“…Such an approach was implemented by the Wang group in which the benzylic cation was intercepted with water to furnish the benzylic alcohol, which underwent additional oxidation to give the corresponding ketone (Scheme 47). 457 Diarylcarbenium ions can successfully be generated and accumulated by low-temperature electrochemical oxidation using the ''cation pool'' method. [458][459][460][461][462][463][464][465][466] In the presence of DMSO, alkoxysulfonium ions serve as the key intermediates.…”
Section: Electrochemical C-h Bond Oxygenationmentioning
confidence: 99%
“…因此在本实验中通过原位生成醛, 进一步发 生氰基化反应是一种更有效的氰化方法. [43,44] , 醛与溶液中的羟胺发生 亲核加成反应生成醛肟 6. 然后, 醛肟在阳极作用下进 一步失去两个电子和两个质子生成腈氧化物中间体 7 [45] , 再经过阴极得到两个电子还原生成目标产物腈 8 [46~48] .…”
Section: 化剂相容的氮源等仍是需面临的问题unclassified